PERBANDINGAN METODE SOMOGYI-NELSON DAN ANTHRONE-SULFAT PADA PENETAPAN KADAR GULA PEREDUKSI DALAM UMBI CILEMBU (Ipomea batatas L.) - Hasanul Kiyan Al-kayyis; Hari Susanti (Sanata Dharma University, 2016)
Sweet potato cultivar Cilembu, kind of rancing from Cilembu Village, Sumedang, West Java has really sweet taste due to the high content of reducing sugar. The amount of reducing sugar needs to be proven scientifically. The study aimed to compare Somogyi-Nelson method and Anthrone-Sulfate method in order to determine reducing sugar level in Cilembu sweet potato. Cilembu sweet potato must be stored in freezer at 15C for 2 weeks before used as the sample. Analytical method validation was performed for the two methods. The determination results between two methods were compared. The amount of reduction sugar (glucose) from Cilembu sweet potato determined by Somogyi-Nelson method was 3.42%, the value of %recovery was 99.8%, LOD = 0.00167 (mg/mL), LOQ = 0.00557 (mg/mL), and value of RSD was 3.7%. While the average amount of reduction sugar determined by Anthrone-Sulfate method was 14.9%, the value of %recovery was 74.7%, LOD = 0.0198 (mg/mL), LOQ = 0.066 (mg/mL), and value of RSD = 8.6%. The Somogyi-Nelson method was more recommended for the analysis of the reducing sugar in Cilembu sweet potato compared with Anthrone-Sulfate method.